Effect of Silane and Silicate based Penetrants against Corrosion of Steel with Partial Cover Thickness - Muhammad Afaq Khalid; Shinichi Miyazato; Tatsuya Minato; Hibiki Mizuguchi (Civil Engineering Journal, 2023)
The partial cover thickness of reinforced concrete structures near the coastline enhances the early corrosion onset, which reduces the service life. As a countermeasure under the preventive maintenance approach, to delay early corrosion onset in structures with partial cover thickness and increase durability throughout the service life, this study used silane and silicate-based surface penetrants. Mortar specimens with a partial cover thickness and embedded, specially segmented bars were prepared. Both penetrants were applied to specimens with partial cover thicknesses (20 and 7.5 mm). Further, electrochemical methods such as macrocell current, microcell current, electric resistivity, and potentiodynamic polarization curves were used to assess the corrosion resistance before and after coating. The penetration depth of silane was measured visually, and the Vickers hardness test was used for the silicate penetrant. The “equivalent cover approach” was adopted to evaluate the performance of penetrants throughout their service lives. Results revealed that the total corrosion current density decreased by 79% for specimens coated with silane and 52% for silicate penetrant, whereas no change was observed in the uncoated specimens. Based on the equivalent cover approach, the silane penetrant was determined to be most effective in delaying the corrosion onset and propagation time for cover thicknesses of 60 and 50 mm at 100 m distance against 70 mm, and for 40 and 30 mm against 50 mm at 250 m from the coastline. Further, the silicate-based penetrant was only effective for a deficient cover thickness of 5 mm against the specified cover thicknesses at a distance of 100 and 250 m from the sea coast. Doi: 10.28991/CEJ-2023-09-12-02 Full Text: PDF